Computation of the Total Acoustic Atmospheric Attenuation Coefficient Aα for Several Acoustic Sources in Tikrit City - Allah, Sabah Mahmoud Aman (Sulaimani Journal for Pure and Applied Sciences, 2013)
In this work, the attenuation coefficients Aα had determined for different acoustic source by the air atmosphere for one day in Tikrit city, based on an analytical method which employed on several empirical equations that taking in consideration the various meteorological conditions in which the climate elements changed in additional to frequencies sources. The results shows the atmospheric attenuation is sensitive to the composition of air, particularly to the wide varying concentration of water vapor and temperature where the air temperature play and frequency variation are dominate that controlling the values of Aα.
Keywords: acoustic attenuation coefficients; Atmospheric absorption; relative humidity; temperature; pressure; Oxygen and Nitrogen relaxation frequencies